(untitled) (Czech Journal of International Relations, 1967)
On January 11, 1987, the Institute for International Politics and Economics hosted a symposium on the role of foreign capital and foreign aid in the economic development of underdeveloped countries. It was attended by 40 female workers from research institutes and from practice. The basic material presented for discussion was the work of the 2nd Svejnar international capital, aid and economic development of developing countries. Of course, the discussion was not limited to comments on this study. In the introduction, which was actually a summary of the already mentioned work, Z. Svejnar effective capital in relation to foreign aid to increase the rate of accumulation and accumulation of already existing resources and explicitly assumed that in developing countries it can in a certain sense lead to combined and extensive growth (considered from the point of view of simultaneous use of labor and capital-intensive techniques). He infuriated further importance of the necessary integration of foreign loans with development plans and tried to criticize research on the effectiveness of foreign countries! help based unilaterally on monitoring the marginal efficiency of capital and the rate of interest. Here, the reporter emphasized the importance of institutional factors and structural reforms, the effects of which (already achieved or potential) cannot be neglected when examining the effectiveness of external sources.